“PROFIL KONDISI FISIK ATLET DAYUNG PORPOV KOTA CIMAHI 2022” - Amrul Hayat (Sekolah Tinggi Ilmu Kesehatan Tujuh Belas, Karanganyar, JAwa, Indonesia, 2022)
This research is a type of descriptive research with a survey method which aims to find out the profile of the physical condition of Porpov rowing athletes in Cimahi City in 2022. To find out the research